ANALISIS BESAR KOEFISIEN GESEKAN DAN ANGKA REYNOLDS TERHADAP VARIASI KEMIRINGAN PIPA TRANSMISI JARINGAN IRIGASI TETES PVC DRIPLINE - I D G JAYA NEGARA; HUMAIRO SAIDAH; FITRAH RIZAL DWIASMORO; ANID SUPRIYADI; LILIK HANIFAH (Universitas Mahasaraswati K. Mataram, 2021)
Farming with drip irrigation systems on sloping dry land is very rarely found at the field level, so that many dry lands are rarely used by the community. To be able to support the application of drip irrigation on sloping land, it is necessary to test the effect of slope variations on the flow characteristics of the drip irrigation system. This study aims to determine the effect of variations in the slope of the transmission pipe, which describes the slope of the land, on the Reynolds number (Re) and the pipe friction coefficient (f) generated in the drip irrigation network. The test drip irrigation network was made of 4 PVC pipes with a distance of 80 cm between the pipes, the drip hole distance of 60 cm and a diameter of 0.5 mm. The test variations are the slope of the transmission pipe 10 °, 20 °, 30 °, 40 ° and the water depth above the outlet tower h1 = 20cm, h2 = 30cm and h3 = 40cm with various head heights. Research using a water source from a tower with a capacity of ± 200 liters with a height of 3.3 m, a transmission line of PVC pipe Ø1 / 2 inches long 3.35 m.The results showed that the Re value will be greater from drip pipe 1 to drip pipe 4. The range of Re values from 1 to pipe 4 is 195 to 992 which is classified as laminar. The amount of friction coefficient f obtained decreases from drip pipe 1 to drip pipe 4, with a value of 0.327 to 0.064.